Evaluation of Airline Service Quality Attributes: The Nigerian Experience (Global Journal of Science Frontier Research, 2017)
Airlines are suffering from such competition Service quality is typically defined regarding consumer satisfaction The purpose of this paper is to provide a better understanding of how satisfaction level among passenger with Arik and Aero Airlines is and how its managers can improve their service quality To reach to achieve this purpose we have studied different models of service quality measurement and adopted Gronroos model as a comprehensive model we developed and adopted it to encompass various aspects of airlines services We inclusively inferred that passengers of Arik and Aero are not satisfied with the perceived services and it warns manager to focus on passengers expectations Tangibles assurance responsiveness reliability empathy image and technical quality are seven features of the model and in all of them passengers feel dissatisfied Managers should treat employees improve visual facilities and coordinate all people departments and organizations involved with the airline Finally with airline must measure passengers satisfaction and service quality seasonally to keep the services corresponded with customers opinions
Keywords: airline; service quality; gronroos model and passenger